COMPUTER TECHNOLOGY OF PROCESSING ARRIVALS OF IMPLEMENTATIONS OF TWO-DIMENSIONAL RANDOM VALUE - Приставка, П. О. (Proceedings of National Aviation University, 2021)
The technology of processing arrays of realizations of two-dimensional random variable is presented: data preparation for processing, non-parametric estimation of density function and probability distribution.